Metode Kritik Matan Hadis Muhammad á¹ªÄhir Al-JawÄbÄ« dalam Kitab: JuhÅ«d al-Muá¸¥addiá¹¡Ä«n FÄ« Naqd Matan al-á¸¤adÄ«á¹¡ an-NabawÄ« asy-SyarÄ«f - Qomarullah, Muhammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2018)
Matan’s criticism is one of the most important studies in the critique of hadith after the criticism of sanad. The importance of matan’s criticism is that the meaning of a hadith is closely related to the validity of matan. Sanad is the support of the hadith component, while the matter of the hadith lies in the matan. In general, the criticism of matan hadith includes three activities or stages: (1) conducting criticism or selection of matan hadith (naqd al-matn), (2) interpretation or interpretation of matan hadis (syarh al-matan), and (3) doing typology or the classification of matan hadis (qism al-matan). This article aims to reveal the method of matan research initiated by Muhammad Thahir al-Jawabi in his book JuhÅ«d al-Muá¸¥addiá¹¡Ä«n FÄ« Naqd Matan al-á¸¤adÄ«á¹¡ an-NabawÄ« asy-SyarÄ«f. Through the method of character study, it was found that the method of criticism of Matan offered by al-Jawabi is to compare (muqaranah). Namely, (1) examine the contradiction of hadith with the Qur’an, (2) examine the contradiction of hadith with the fatwa of shahabah, (3) to examine the contradiction of hadith with the knowledge of history